The neuroprotective effect of cannabidiol is enhanced by resveratrol and alpha-lipoic acid in social isolation - Ricciardi, Federica; Morace, Andrea Maria; Limongelli, Rebecca; Iannotta, Monica; Boccella, Serena; Fusco, Antimo; Bonsale, Roozbe; Perrone, Michela; Infantino, Rosmara; Di Martino, Emanuele; Mattia, Consalvo; Gargano, Francesca; et al. (Frontiers in Pharmacology, 2025)
IntroductionPost-traumatic stress disorder (PTSD) is a chronic psychiatric condition characterized by persistent cognitive and affective disturbances following exposure to severe trauma. In rodents, prolonged post-weaning social isolation is a well-established model of PTSD-like symptomatology. In this study, we investigated the behavioral effects of chronic cannabidiol (CBD) administration—either alone or in combination with two natural antioxidants, resveratrol (RES) and alpha-lipoic acid (ALA)in socially isolated mice.MethodsMale CD1 mice (n = 8) were isolated in individual cages from postnatal day 21 (PN21) and maintained in isolation for 30 days. They were then treated with CBD (2.5, 5, and 10 mg/kg), resveratrol (RES, 20 mg/kg), or alpha-lipoic acid (ALA, 10 mg/kg) for 15 days following social isolation.ResultsWhile low-dose CBD (2.5 mg/kg) alone was ineffective, its combination with either RES or ALA restored the latency to the first attack and significantly reduced aggressive behavior, comparable to high-dose CBD (10 mg/kg). Similarly, combined treatments with RES or ALA markedly reduced immobility time in the tail suspension test, indicating antidepressant-like effects. In contrast, no significant anxiolytic effect was observed with the combinations in the hole-board test, suggesting a limited action on anxiety-like behavior.DiscussionThese findings suggest that co-administration of CBD with RES or ALA exerts synergistic antidepressants and anti-aggressive effects in a PTSD-like model, potentially allowing for dose reduction of CBD. Further studies are warranted to explore the underlying molecular mechanisms.